Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 3304083 species occurrences available in GBIF matching the query: { } The dataset includes 3304083 records from 32454 constituent datasets: 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 4 records from Microplankton counts and carbon biomass at station TT007_10-CTD123. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 3975 records from Study on plankton at the port of Ostend in 1965. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 162 records from Inventario forestal de una parcela permanente de restauraci?n en el Parque Nacional Natural Alto Fragua Indi Wasi, en la vereda La Estrella, Caquet?. 20 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 2 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, M?xico. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 2 records from First description of the female of Clubiona milingae Barrion-Dupo, Barrion & Heong, 2013 (Araneae, Clubionidae). 239 records from Hidden in plain sight: reassessment of the pig-footed bandicoot, Chaeropus ecaudatus (Peramelemorphia, Chaeropodidae), with a description of a new species from central australia, and use of the fossil record to trace its past distribution. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China. 72 records from Amphibian and Reptile species occurrence records in the Tana River Basin, Kenya. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 15 records from Review of the genus Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from North America, with description of P. (P.) subletteorum sp. nov.. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 1702 records from BioGIS - Bryophytes - HUJ collections. 3 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 46316 records from Future climate change affects the microbiome and condition of habitat-forming kelp. 457 records from (Appendix B) Dinoflagellate cysts in ODP Site 170-1039 sediments. 32602 records from The Brown University Foraminiferal Data Base (BFD). 958 records from Collection de longicornes et autres col?opt?res saproxyliques de Lionel Valladares. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 55 records from Caracterizaci?n faun?stica de la Reserva Forestal Protectora Regional Brisas del Rinc?n. 871 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23?S and 44?S. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 352 records from Universidad del Valle de Guatemala - Colecci?n de Artr?podos. 34 records from National System of Protected Areas in Poland - Fungi. 64 records from Pilzlehrwald. 2208 records from marine sediment metagenome Raw sequence reads. 2 records from Loneura Nav?s (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colecci?n Zool?gica Universidad del Tolima (CZUT) - Ar?cnidos. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 776 records from Programme ACT : R?partition Pie bavarde 2010 - 2014 Coordonn?es GPS Lambert 93. 106 records from Abundance of radiolaria at station UT99-5-1. 144 records from Donn?es naturalistes de Xavier BONNET. 16 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 330046 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 44 records from Flora und Fauna in unserer Kita. 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 1015 records from Programme ACT : R?partition Merle noir 2005 - 2009 Coordonn?es GPS Lambert 93. 43 records from Abundance of coccosphere-units of sediment core GIK23424-3. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 6 records from Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific. 103 records from Foraminifera species abundances from tow TT011_5-MOC63. 8 records from New Polypheretima and Pithemera (Oligochaeta: Megascolecidae) species from the Mt. Malindang Range, Mindanao Island, Philippines. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 8 records from Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae). 2445 records from Flore des Pyr?n?es. 14 records from Collection Amphibia fossil SMF. 164 records from Total foraminifera counts of multinet M6/7_MSN100. 12681 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb). 22 records from A description of the flea species Paractenopsyllus madagascarensis n. sp. and the female sex of Paractenopsyllus raxworthyi Duchemin & Ratovonjato, 2004 (Siphonaptera, Leptopsyllidae) from Madagascar with a key to the species of Paractenopsyllus. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservaci?n Guanacaste in northwestern Costa Rica, with a key to their identification. 8862 records from Donn?es naturalistes de Benoit MARTHA. 114 records from Especies de peces registradas en el canal principal y afluentes de los r?os Lengup? y Up?a en Boyac?. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 121778 records from Observations occasionnelles Parc national des Pyr?n?es. 6 records from A contribution to the knowledge of Dermestidae (Coleoptera) from Guatemala. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 120 records from BIRDRACE The early birds. 2132 records from Donn?es odonates collect?es par le CEN Aquitaine entre 1995 et 2015. 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 4 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 1151 records from Records of the Victorian Conservation Seedbank. 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 3 records from Microlaimus capitatus sp. n. and Dichromadora simplex Timm, 1961 (Nematoda, Chromadorea) from the coast of Vietnam. 54 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 193 records from Relative abundances of Florisphaera profunda and Helicosphaera carteri during the sapropel S5 of sediment core MD81-LC21. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 115 records from Antarctic Pycnogonids II. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 105 records from Microfossil abundance of Hole 18-173. 1456 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 539 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 6979 records from Upper Silesian Museum, Bird Observations. 252 records from Total foraminifera counts of multinet M6/7_MSN91. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 847 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 14110 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 269 records from SEWBReC Springtails and allies (South East Wales). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 860613 records from Collation of spatial seagrass data from 1984 - 2014 for the Great Barrier Reef World Heritage Area (GBRWHA) (NESP TWQ 3.1, TropWATER, JCU), Australia (1984-2014). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_12-CTD147. 28934 records from Pacific Reef Assessment and Monitoring Program: Rapid Ecological Assessments of Fish Large-Area Stationary Point Count Surveys (SPC) at Coral Reef Sites across the Pacific Ocean from 2000 to 2007. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 749 records from Carabidae of Wales and England. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 16 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 131 records from Artenvielfalt auf dem Schulgel?nde. 100 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 5 records from Two new littoral species of the genus Anurida Laboulb?ne, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 58 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1391. 8425 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 36 records from Triticale French National Collection. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 7918 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 69 records from BIRDRACE Pfeifenten. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 5335 records from Marine metagenome ICM_JRV. 188 records from Donn?es de la structure ONEMA/AFB provenant de la base de donn?e du SINP ?le-de-France CETTIA. 147 records from Donn?es de la naturaliste Laurence Beauchamp. 322 records from Collections ichtyologiques et herp?tologiques (BOUM). 23 records from The world species of Ophthalmothrips Hood (Thysanoptera; Phlaeothripidae), with new records from Africa, China and Japan. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 126 records from Bryological collection of Yugra State University. 27 records from Bemerkenswerte Faltenwespen aus der ?thiopischen Region. Teil 14 (Hymenoptera, Vespidae, Eumeninae). 276503 records from hymenoptera. 143 records from (Table 1) Middle Eocene silicoflagellates from DSDP Hole 95-612. 1110 records from FFH-Gebiet "Calwer Heckeng?u". 389 records from Amphibian and Reptilian (KIEE-AR). 813 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE233. 858 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 232 records from Filogenia de las cact?ceas columnares (Pachycereeae) con base en caracteres anat?mico-morfol?gicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79? N section). 5919 records from Cat?logo taxon?mico y biogeogr?fico de los radiolarios (orden Polycystina) de la regi?n central y sur del Golfo de California. 1395 records from Birds - Wild Birds (KIDR-BI). 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 139 records from Revision of the subgenus Stigmatophorella of Chalcophorella (Coleoptera: Buprestidae: Chrysochroinae). 55 records from The Genus Daspletis Loew, 1858 And The Description Of Two New Genera, Anasillomos And Remotomyia (Diptera: Asilidae: Stenopogoninae). 4 records from A new rotifer species: Lecane langsenensis n. sp. (Rotifera: Monogononta) from Vietnam. 41100 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 81532 records from Bob Merritt Coleoptera Dataset. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 22 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 14141 records from Mise en place d'un suivi scientifique des rhopaloc?res pour la production d?indicateurs de biodiversit?. 1045440 records from CLICNAT Base de donn?es naturaliste picarde g?r?e par Picardie Nature. 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 413272 records from DATAVES. 109 records from Projet Diable de mer - AILERONS. 150 records from Mam?feros no voladores de las sabanas inundables de las cuencas de los r?os Bita, Manacac?as y Cravo Sur - SULU II. 27 records from (Table S2) Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 161-975D. 649 records from Beetles from nature reserves and nearby forests in ?stmarka. 28 records from Caracterizaci?n de la fauna del p?ramo del Duende, litoral del San Juan, Choc?. 40 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 1 records from Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic. 4975 records from Radiolaria specimens from the Norwegian Sea and Arctic Ocean. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 135 records from Planktic foraminifera abundance of Hole 73-524. 7 records from Planktic foraminifera abundance of Hole 53-418B. 19 records from Distribution Data for Megachile chomskyi. 352 records from Flora vascular y no vascular: expedici?n Monte y Pinal - Proyecto Boyac? BIO UPTC. 25987 records from Berea College, Ralph L. Thompson Herbarium. 1 records from Beitrage zur Kenntniss pal?arctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1012 records from Programme ACT : R?partition Merle noir 2011 - 2015 Coordonn?es GPS Lambert 93. 175 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 409 records from Distribution of nanoplankton at trap WR2. 54 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 3 records from A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia. 15 records from A review of the Blaesiina (Coleoptera, Scarabaeidae, Cetoniinae, Gymnetini). 4520 records from Donn?es d'observation de la m?gafaune marine issues des campagnes oc?anographiques en France m?tropolitaine. 642 records from An?lisis de la biodiversidad y servicios ecosist?micos para su aplicaci?n en la toma de decisiones en el departamento de Boyac?/Boyac? Bio-Flora El Consuelo. 382 records from Chronicle of Nature - Phenology of Plants of Bryansk Forest Nature Reserve. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 98 records from Gew?sser des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-W?rttemberg). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_3-CTD37. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 17 records from Marine metagenome ICM_AGW. 15397 records from Macrophyte Lake Data. 78 records from Donn?es de la naturaliste Anna Even. 2512 records from Donn?es du Busard de Maillard (Circus maillardi) du Parc national de La R?union. 6253 records from Siliceous microfossil occurrence, Site 177-1091. 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 816 records from Esp?ces v?getales sur sable roux du fourr? de Ranobe, PK 32 Toliara. 1 records from Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China. 59 records from Colecci?n Herpetol?gica-Museo de Historia Natural Unillanos. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 601 records from Range table from benthic foraminifers in ODP Hole 149-900A. 1 records from On the Chilopoda from Turkey. 4 records from Proposal of Marbefia, gen. n. and Inermiphonte, gen. n., including updated keys to the species of Pseudonychocamptus Lang, 1944 and Paralaophonte Lang, 1948 (Copepoda, Harpacticoida, Laophontidae). 145 records from Revision of Telothyria van der Wulp (Diptera: Tachinidae) and twenty-five new species from Area de Conservaci?n Guanacaste in northwestern Costa Rica with a key to Mesoamerican species. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 95 records from Kystfuruskoger i Tysnes og Fusa. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avan?ats de Blanes, Macroinvertebrados Limno. 407 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 447 records from Estudio ecol?gico-flor?stico de los enclaves de vegetaci?n xerof?tica inmersos en una selva baja caducifolia en el Istmo de Tehuantepec, Oaxaca. 87 records from Diatom abundance of Hole 95-613. 62125 records from UCLA Donald R. Dickey Bird and Mammal Collection. 2364 records from Modelaci?n de la distribuci?n geogr?fica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 13 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-09-1. 3 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 7 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 11147 records from Collections of Bioclass, school #179, Moscow. 580 records from Donn?es du/de la naturaliste Houpert Sylvain provenant de la base de donn?e du SINP ?le-de-France CETTIA. 705008469 records from EOD - eBird Observation Dataset. 1 records from Arcanumophis, a new genus and generic allocation for Erythrolamprus problematicus (Myers 1986), Xenodontinae (Colubridae) from the Cordillera de Carabaya, southern Peru. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the B?rzs?ny Mountains, Hungary. 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 4 records from A new species of Agapophyta Gu?rin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 14 records from New seriated Amathia species in Japan, with a redescription of A. acervata Lamouroux, 1824 (Bryozoa: Ctenostomata). 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mam?feros, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedici?n cient?fica en la ventana Mesay en el sector sur del Parque Nacional Natural Serran?a de Chiribiquete. 206 records from Gross body measurements of Antarctic Rock Cod (Trematomus bernacchii) collected at sites adjacent to Casey Station 2012/13. 4 records from Dinoflagellate abundance of Hole 14-144. 282 records from Middlebury College Bee Collection. 43 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 307397 records from Digitalizaci?n y sistematizaci?n de las colecciones biol?gicas del INECOL (Herbario). 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 953 records from Occurrence of bees along grazing and agricultural gradients in Northern Tanzania. 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 167 records from Total foraminifera counts of multinet M21/6_MSN787. 231 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 3 records from New species of Alpinalona Alonso & Sinev, 2017 (Cladocera: Anomopoda: Chydoridae) from South-East USA. 218 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 11 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 184 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part II. 8 records from Benthic macrofauna abundance of sediment core 12930-063. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 74123 records from IAN herbarium - Embrapa Amaz?nia Oriental - Herb?rio Virtual REFLORA. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carri?re from China (Hemiptera, Cicadellidae). 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 526 records from FernsDarwinCore. 13 records from Grupo de Macroinvertebrados de la laguna Cristalina P?ramo de la Rusia-Boyac?.. 46416 records from The Taiwan Roadkill Observation Network Data Set.. 222 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 220 records from Donn?es naturalistes de Ing?nieurs ?cologues GEREA. 5 records from Note on the genus Lecanophryella (Ciliophora: Suctorea) with description of a new species from west coast of India. 124 records from Distribution And New Records Of Lymexylidae (Coleoptera: Lymexyloidea) In Guatemala And Mexico. 8046 records from sediment metagenome Metagenome. 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 ?m). 1158 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 5 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 1543 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 2059 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 18 records from Naturtag. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 73 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 14 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 29 records from Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae) including new species and biological information. 1709 records from suspended particulate matter Raw sequence reads. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 4 records from Taxonomic revision of the Neotropical genus Ectophasiopsis Townsend, 1915 (Diptera: Tachinidae: Phasiinae). 47 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 607514 records from Plant. 207 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 31 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 50 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 21 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 123 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Sch?ffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (St?l, 1860) and revalidation of P. fuscescens (Dallas, 1851). 128 records from Pollen profile 2 from Richland Creek. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 363 records from Donn?es du/de la naturaliste Kohn Annie provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1916 records from Donn?es naturalistes de la Soci?t? pour le Mus?um d'Orl?ans et les Sciences (SOMOS). 79238 records from Inventaire de la flore de Dordogne 2017. 4343 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 24 records from Chapter 7: Linnaean Plant Names and their Types (part Q). 5168 records from (Table 9) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-587. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 15 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 24 records from Steinbruch Mainz-Weisenau, 4.Jahr. 12859 records from Colec??o Entomol?gica IIA. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 17155 records from MZFC/Coleccion de Aves. 1190 records from Cole?pteros presentes en un proceso de restauraci?n pasiva en bosque seco tropical. 114567 records from TNHC Herpetology Collection. 1292 records from (Table 4) Benthic foraminifera in middle to late Miocene sediments of DSDP Hole 90-588. 143 records from Foraminifera abundance of Hole 48-406. 354 records from Avifauna asociada a los manglares de Tribug? - Nuqu?, 2016. 1121933 records from Tasmanian Natural Values Atlas. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 89 records from ZUEC-POR - Cole??o de Porifera do Museu de Zoologia da UNICAMP. 625 records from Inventario de la biota terrestre (flor?stico) y marina (invertebrados, peces y macroalgas bent?nicos) del parque nacional Isla Isabel (Plantas). 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 521 records from Benthic foraminifera abundance of Hole 82-558. 940 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 7148 records from DMNS Egg Collection (Arctos). 495 records from USFWS Bee surveys - Sandbar WMA, VT 2018. 146 records from Colecci?n de moldes endocraneanos del CENPAT. 20 records from Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 3062 records from University of Vermont, Pringle Herbarium, Algae Collection. 23 records from Abundance of benthos infauna at station GIK23042-2. 68 records from Streuobstwiese. 296 records from (Table AT9) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134B. 44 records from Description of lithologic section units of IODP Hole 325-M0041A. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 16 records from Revision of the euryglossiform species of the Afrotropical bee genus Scrapter Lepeletier & Serville, 1828 (Hymenoptera: Apoidea: Colletidae). 58 records from Range table from benthic foraminifera in ODP Hole 199-1220A. 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 19619 records from Carabidae of the Carpathians. 23 records from The Phalacridae (Coleoptera, Cucujoidea) of Canada: new records, distribution, and bionomics with a particular focus on the Atlantic Canadian fauna. 2591 records from 1848-1982 Lundy Field Society The Marine Fauna of Lundy. 82 records from R?ckkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 ?m fraction. 247 records from Flora vascular y no vascular: expedici?n Cuenca Media del r?o Chicamocha - Proyecto Boyac? BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 8 records from An overview of Scirtidae (Coleoptera) described by Antoine Joseph Jean Solier (1792 - 1851). 2785010 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 15883 records from Canadian Lakes Loon Survey. 7 records from Two New Species of Composetia (Annelida: Nereididae) from Small Estuaries in the Ryukyu Islands, Southern Japan, with a List of All Species Currently Belonging to Composetia. 13 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1009 records from Programme ACT : R?partition Merle noir 2012 - 2016 Coordonn?es GPS Lambert 93. 591 records from Alan Wormington Collection. 93 records from Benthic Foraminifera from the Capricorn Group, Great Barrier Reef, Australia. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 33403 records from Colecci?n de Entomolog?a del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris ?ur?i?. 642 records from Protistan plankton diversity along salt gradient. 5 records from Revalidation of a moray eel, Gymnothorax mucifer Snyder, 1904 (Teleostei: Anguilliformes: Muraenidae), with a revised distribution. 4617 records from Inventaire de la flore du Grand Poitiers 2009. 378 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 4639 records from UAM Herbarium (ALA), Algae Collection (Arctos). 374 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 8565 records from Colecci?n de insectos agr?colas del proyecto diversidad en sistemas de cultivos. 1 records from A new genus of mongoliulid millipedes from the Far East of Russia, with a list of species in the family (Diplopoda, Julida, Mongoliulidae). 1785 records from 3Soil16S. 60102 records from Geneva Herbarium ? De Candolle's Prodromus (G-DC). 91 records from Distribution of planktic foraminifera (250-500 ?m) of box sediment core PS1246-2. 2579 records from Donn?es de la structure ANCA (les Amis Naturalistes des Coteaux d'Avron) provenant de la base de donn?e du SINP ?le-de-France CETTIA. 750 records from Museu Valenci? d?Hist?ria Natural - Fundaci?n Entomol?gica Torres Sala: FETS. 53 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 4 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 30 records from Nannofossil abundance of Hole 24-233A. 470 records from Gross body measurements of Laternula elliptica collected from sites adjacent to Casey Station 2014/15. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 9 records from The identity of Aplocheilus andamanicus (K?hler, 1906) (Teleostei: Cyprinodontiformes), an endemic Killifish from the Andaman Islands, with notes on Odontopsis armata van Hasselt. 231 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 13 records from Synonymies, new records, and new species in Cerambycinae (Coleoptera Cerambycidae). 233 records from Monitoreo biol?gicos en la cuenca Frayle, ARA - RARE - CVC ? Asociaci?n Calidris. 236 records from Planktic foraminifera counts of sediment core RC11-134. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribuci?n de la Nutria (Lontra longicaudis) en la cuenca baja del r?o Sin? en el departamento de C?rdoba. 3 records from One new species of the subgenus Xizicus (Zangxizicus) (Orthoptera: Tettigoniidae: Meconematinae) from China. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 408 records from Birds Specimens of Akita Prefectural Museum. 516 records from Planktic foraminifera counts of sediment core A15-558. 12 records from Urochordeumatidae Silvestri, 1909, a millipede family endemic to Washington State, USA (Chordeumatida, Striariidea, Striarioidea). 2191 records from Actualizaci?n de la base de datos de crust?ceos y registro de datos de peces del pac?fico mexicano de la Colecci?n Biol?gica de la Secretar?a de Marina (Crust?ceos). 102 records from Donn?es du naturaliste JAPIOT Xavier provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 101 records from Donn?es naturalistes de LE GLOANEC Vincent. 136 records from Oberes Schindelbachtal. 84 records from SNH Invertebrate Site Condition Monitoring 2015: Dunhog Moss SSSI. 177831 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-78. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 185 records from Size of planktic foraminifera at CTD station PS55/051. 1 records from Juvenile eucladid crinoid from the Middle Devonian of Turkey. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 445 records from Propuesta de diagn?stico, erradicaci?n y monitoreo post-erradicaci?n, de especies ex?ticas invasoras en oasis de Baja California Sur, centr?ndose en las dos m?s relevantes: rana toro Lithobates catesbeianus y manto de cristo Cryptostegia grandiflora. 7122 records from Whale catches in the Southern Ocean. 9 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 407 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 8 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 14860 records from Floristic diversity of the protected areas of Mont Kouff? and Wari Maro in the north of Benin. 7 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 134 records from Mycoblitz 2017 - IRBV et Cercle des Mycologues de Montr?al. 460 records from pteri4t2017. 3145 records from PCE/TCE dechlorinating microbial community and dehalogenase genes from Wonju Stream, South Korea. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 3326 records from Plant specimens of Nasunogahara Museum. 230 records from Biometr?a peces Parque Nacional Natural La Paya. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 95 records from Anfibios y reptiles de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 1933 records from An?lisis de Integridad Biol?gica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 32 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 13868 records from Donn?es faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-V?gel (VFV). 417 records from Benthic foraminifera counts of sediment core GIK23351-1. 11 records from Benthic macrofauna abundance of sediment core 13077-063. 24 records from Taxonomic revision of Australian Amobia Robineau-Desvoidy, 1830 (Sarcophagidae: Miltogramminae): integrating morphology and genetics finds a new species and tackles old problems. 1889 records from Diatomeas bent?nicas de los oasis de Baja California Sur. 4591 records from WII Herbarium Dataset. 53 records from Donn?es du/de la naturaliste Dubois Yves provenant de la base de donn?e du SINP ?le-de-France CETTIA. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 36175 records from Quaid-i-Azam University Herbarium. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 756 records from (Table 4) New palynological record of sediments from Odderade. 18 records from Anfibios presentes en el Cerro J?nano. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 26389 records from Protist Diversity in the East China Sea. 120 records from Donn?es esp?ces - Expertise IPE 79. 1715184 records from NBIS Records to December 2016. 27 records from Planktic foraminifera abundance of Hole 51-417B. 64 records from Carrion beetles (Coleoptera, Silphidae) of Volga-Kama Nature Reserve. 118 records from Nezara viridula records held by the Royal Horticultural Society. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 1 records from The giant ? penis ? of a newly described species in the subgenus Scotoconiopteryx from Peru (Neuroptera: Coniopterygidae: Coniopteryginae: Coniopteryx). 16 records from Donn?es naturalistes de ROLLAND Blandine. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 2 records from Description of the female of Dicterias atrosanguinea Selys 1853, with notes on male genital ligula and male behavior (Odonata: Dicteriadidae). 8237 records from Naturalis National Natural History Museum (NL) ? Pisces_Cichlidae of Lake Victoria. 50 records from La Paya, censo r?pido de la flora de Jirijiri. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 32 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6192 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 74 records from Taxonomy and Biogeography without frontiers ? WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 3 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 25 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 11 records from On the Bennelongia nimala and B. triangulata lineages (Crustacea, Ostracoda) in Western Australia, with the description of six new species. 6 records from Coccoliths in sediment core PS1532-9. 270 records from bmhs_weatherheadshell_collection. 57919 records from Fichier communal des ongul?s. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_15-CTD162. 103 records from Morphological and anatomical investigation of New Caledonian graminoid Dendrobium (Orchidaceae) with the description of two new species. 4298 records from ColRest_Raw1. 34 records from Chronicle of Nature - Phenology of Arachnids of FSBI Zeya State Nature Reserve. 15 records from Nannofossil abundance of Hole 4-25. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 57 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 5998 records from SNH Bat Casework records 1970-2007. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 11 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 9176 records from R?seau de surveillance Polynesia Mana - Peuplements de poissons. 1708 records from Chronicle of Nature - Phenology of Plants of Kaniv Nature Reserve. 220 records from Living Cirripedia. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 1284 records from Donn?es du/de la naturaliste Barande Serge provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 555992 records from flora&fauna(NIBR)2019. 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125?m across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 222 records from Land and freshwater molluscs of Northern Spain. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3775 records from Donn?es naturalistes de Charlotte PICARD. 4 records from Ostracoda abundance of Hole 44-390. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 1793 records from Herbarium BSG Lichenes. 3 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 30052 records from University of California Santa Barbara Invertebrate Zoology Collection. 32 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 26 records from Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific). 2227 records from IRAD Cameroon insect collection. 1156 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 463 records from Mammif?res (sauf Chiropt?res) du Mus?um d'Histoire Naturelle de la ville de Bourges (BOUM). 9 records from Redescription of Isotoma grana Lee, Kim & Kim, 1993 and description of a new species of Isotoma Bourlet, 1839 (Collembola: Isotomidae) from Korea. 157 records from Nannofossil abundance of Hole 94-610B. 20170 records from Vertebrados terrestres del Corredor Biol?gico Sierra Madre del Sur, Chiapas, M?xico. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 6390 records from Colecci?n de Fabales del Museo Bot?nico CORD - IMBIV. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 100 records from Total foraminifera counts of multinet M21/2_MSN644. 4 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 120231 records from ALCB - Herb?rio Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 9 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 128557 records from Fish specimens of Kagoshima University Museum. 245 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 13662 records from UTEP Invertebrates (Arctos). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 11 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 5 records from A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Ba Den Mountain, Tay Ninh Province, southern Vietnam. 163 records from Relative abundance of coccosphere-units at site GIK23414. 521 records from Tentaculata collection of National Museum of Nature and Science. 292 records from Monitoreo y recolecci?n de la diversidad de razas de ma?z criollo en la regi?n de la Huasteca en M?xico para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 833709 records from AMNH Bird Collection. 2756 records from Donn?es du/de la naturaliste Chevallier Laurent provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3621 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversit? et distribution de quelques esp?ces de plantes agroforesti?res au B?nin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 5 records from Psychotria niauensis sp. nov. (Rubiaceae), esp?ce calcicole end?mique de la Polyn?sie fran?aise, d?crite de l?atoll soulev? de Niau (Tuamotu). 817 records from DOW-2. 6 records from Redescriptions of three species of Pulvinaria (Hemiptera: Coccomorpha: Coccidae) in Japan. 30 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 15 records from Nannofossil abundance of Hole 10-93. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 1422 records from Donn?es du/de la naturaliste Chevreau David provenant de la base de donn?e du SINP ?le-de-France CETTIA. 317 records from Base de datos de las especies maderables del g?nero Dalbergia en M?xico, registros del Herbario Nacional de M?xico (MEXU). 2099 records from BioBlitz Barcelona 2010-14. 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 43 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 38 records from Ours 2006 pr?sence Occasionnelle Mailles 10km LAEA R?seau Ours brun ONCFS. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 275 records from Planktic foraminifera counts of sediment core V14-77. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 50 records from Herpetofauna de la expedici?n Pisba - Proyecto Boyac? BIO UPTC. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1677 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 2826 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 931 records from South American Antarctic Marine Biodiversity Literature. 7 records from Inventario de Murci?lagos en la Finca la Reserva, El Perico, Yopal, Casanare. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from M?tropole_Nice_C?te_d'Azur_2017_12_18. 472 records from Blue Mountains Swamp Archaea. 1 records from Beitrage zur Kenntniss pal?arctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 8 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 911 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 51 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 1479 records from Epiphytic mosses from the northwest Iberian quadrant (Spain). 2 records from The origin and evolution of the Tyrannosaurids, Part 1. 1930 records from Donn?es de la naturaliste Lemoine Delphine provenant de la base de donn?e du SINP ?le-de-France CETTIA. 18 records from Thirteen new records of ferns from Brazil. 713 records from Modelaci?n de la distribuci?n y abundancia de las subespecies de venado cola blanca en M?xico: implicaciones de conservaci?n y manejo. 30792 records from ASE herbarium - Universidade Federal de Sergipe - Herb?rio Virtual REFLORA. 384 records from Marine metagenome ICM_AWP. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 33 records from Occurrence of mammalia relicts at site Sveduv stul. 202661 records from The reptiles and amphibians collection (RA) of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 3968 records from Distribution of planktic foraminifera of sediment core M35027-1. 67198 records from FKSE-Herbarium of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 6 records from A new Dondice Marcus Er. 1958 (Gastropoda: Nudibranchia) from the Mediterranean Sea reveals interesting insights into the phylogenetic history of a group of Facelinidae taxa. 121 records from Foraminifera abundance of sediment core IN68-28. 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 6 records from Three new species of trigonopoid Platynotina (Tenebrionidae: Pedinini) from the Baviaanskloof Nature Reserve, South Africa. 102 records from Abundance of planktic foraminifera at CTD station M39/4_352CTD-11. 332 records from Colecci?n de chinches (Insecta: Hemiptera) del Centro de Colecciones Biol?gicas de la Universidad del Magdalena. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 4 records from Mycale (Aegogropila) antiae sp. nov. (Demospongiae; Poecilosclerida; Mycalidae) from Galicia (NW Iberian Peninsula). 16 records from Phenological Center - Fishes (Murmansk). 358 records from Comunidad fitoplanct?nica presente en la Bah?a de Buenaventura 2018. 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 1 records from Aves Argentinas / Asociaci?n Ornitol?gica del Plata - Colecci?n de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 351778 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 886 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 223486 records from Phytochorologie des d?partements fran?ais. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 244381 records from Carnet B Lorraine. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 361010 records from Seasearch Marine Surveys in England. 35 records from Planktic foraminifera abundance of Hole 84-566C. 17 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 25 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 14009 records from Collection Trichoptera - SMF. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 751 records from Planktic foraminifera abundance of Hole 27-262. 1798 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 35 records from Planktic foraminifera abundance of Hole 27-260. 126934 records from Arizona State University Hasbrouck Insect Collection. 3618 records from Fonoteca Zool?gica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 429 records from Collection Strepsiptera SMF. 77 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3363 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetol?gica Chetumal). 124 records from Birdrace-Die_Ackerm?nnchen-Schalm-Eder-Kreis. 57 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 457 records from Helmintos par?sitos de peces dulceacu?colas de cuencas hidrol?gicas del Centro-Norte de M?xico (Durango). 87901 records from MDFRC macroinvertebrate survey. 128 records from Inventaire des reptiles 2014. 10 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 2 records from Gladiopycnodontidae, a new family of pycnodontiform fishes from the Late Cretaceous of Lebanon, with the description of three genera. 589 records from Programme ACT : R?partition Pie bavarde 2005 - 2009 Coordonn?es GPS Lambert 93. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 29412 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 9 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 9373 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from Tripylella australis sp. nov. and Tripyla setifera B?tschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des esp?ces v?g?tales du sous bois des plantations de Teck de la for?t naturelle de la Lama. 411 records from SuLaMa reptile survey I 2012. 61 records from Shrews of Poland. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 9 records from Nannofossil abundance of Hole 2-11. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 191 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 2371 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 238 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 15 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 29876 records from European Moth Nights. 172 records from Donn?es du/de la naturaliste Roquinarc'h Oc?ane provenant de la base de donn?e du SINP ?le-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 6779 records from Donn?es du naturaliste MIGUET Pierre provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 1462 records from Colecta bot?nica: ?rea maya regi?n de la Reserva Calakmul, Campeche. 1036 records from BUND - Dassower See (L?beck/Dassow). 59995 records from Donn?es naturalistes de Monsieur Fran?ois FOURNIER. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 54402 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from S?chsische Schweiz (Wehlener Gebiet). 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 22 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 29 records from Ours 2004 pr?sence Occasionnelle Mailles 10km LAEA R?seau Ours brun ONCFS. 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 8 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 40 records from Planktic foraminifera abundance of Hole 14-137. 2545 records from UWYMV Bird Collection (Arctos). 752 records from Donn?es naturalistes de Monsieur JOURDE R?mi. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 ?m. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 3 records from Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae). 5 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 18 records from Aves Argentinas / Asociaci?n Ornitol?gica del Plata - Colecci?n de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 96 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Choc? forest of Ecuador, with the description of thirteen new species. 1 records from A new species of Centrouropoda (Acari: Uropodidae: Uropodina), with a key to the world species of the genus. 13736 records from MfN - Mallophaga Collection. 2 records from Synchrotron micro-CT scanning leads to the discovery of a new genus of morphologically conserved echinoid (Echinodermata: Cassiduloida). 5 records from Nannofossil abundance of Hole 6-53A. 12 records from Nannofossil abundance of Hole 29-283A. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 5262 records from Spider Mites Collection of Jean Gutierrez. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 1 records from A new name for Dendronephthya kukenthali Gravier, 1908 (Octocorallia, Nephtheidae): Dendronephthya perezi nom. n.. 15 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 26 records from Schulteich Heinrich-Mann-Schule. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 505 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 115 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 439 records from Implementaci?n de la bioindicaci?n en el R?o Magdalena. 6191 records from marine sediment metagenome Metagenome. 3310 records from Dados da ocorr?ncia de plantas lenhosas em uma cronossequ?ncia em ?rea de Caatinga, Parque Nacional do Catimbau, Bu?que, PE, Brasil. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1971 records from Estudio flor?stico de los bosques mes?filos de la Sierra Mazateca de Oaxaca, M?xico. 371 records from Bannwald Burghauser Forst. 948 records from Bulletin du Mus?um d'Histoire Naturelle [1895- ]. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 293389 records from R. L. McGregor Herbarium Vascular Plants Collection. 13 records from Coccolith counts of multinet M32/5_MSN988. 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 1140 records from Phytoplankton abundance in surface water during Professor Vodyanitskiy cruise PV30_1. 235 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Helmut Dalitz. 15198 records from (Appendix 4) Distribution of benthic foraminifers, living, dead, and total assemblage counts, and faunal diversity in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1889 records from Modelaje de la Distribuci?n geogr?fica de Pinus pseudostrobus y P. leiophylla. 825 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 18 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartem?wen. 3 records from Two new species and the molecular phylogeny of eight species of Macrostomum (Platyhelminthes: Macrostomorpha) from southern China. 2423 records from SANT-Bryo. 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 538 records from Composici?n flor?stica y estructura de una parcela permanente en bosques h?medos tropicales del municipio de Pie de Pepe, Choc?. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2497 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 4 records from Re-visiting the Aphidius urticae s. str. group: re-description of Aphidius rubi Star? and A. silvaticus Star? (Hymenoptera: Braconidae: Aphidiinae). 864 records from Caracterizando la diversidad de especies con c?digos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un ?rea natural protegida mexicana. 125 records from Review of the genus Meganola Dyar, 1898 (Lepidoptera: Nolidae, Nolinae) from Korea, with the description of a new species. 2534 records from Elaboration de table de tarif de cubage multisp?cifique (I). 1 records from The cumacean genus Iphinoe (Crustacea: Peracarida) from Italian waters and I. daphne n. sp. from the northwestern Adriatic Sea, Mediterranean. 2 records from A new tropical montane firefly genus and species, active during winter and endemic to the southeastern Atlantic Rainforest (Coleoptera: Lampyridae). 18940 records from Cowan Tetrapod Collection - Mammals. 20 records from High diversity and endemism in the genus Cautires Waterhouse, 1879 (Coleoptera: Lycidae) from the Malay mountain forests, with the descriptions of fourteen new species. 1818 records from Actualizaci?n de la informaci?n sobre los ma?ces criollos de Oaxaca. 541 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 205 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 911 records from Phytoplankton abundance in surface water in May 1996, Pisco, Peru. 825 records from Pollen profile ADR309. 146 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 2 records from Zorotypus weiweii (Zoraptera: Zorotypidae), a new species of angel insects, from Sabah, East Malaysia. 16 records from Insect Collections of Okomu National Park- Nigeria. 291402 records from ARABEL - Arachnologia Belgica. 133650 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 13 records from Papuacocelus papuanus n. gen., n. sp. a new Eurycanthinae from Papua New Guinea, with notes on the genus Dryococelus Gurney, 1947 and description of the egg (Phasmatodea: Phasmatidae: Eurycanthinae). 494 records from (Table 6) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 2872 records from Tableaux de pr?l?vements communaux. R?seau Ongul?s sauvages ONCFS-FNC-FDC. 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 2707 records from Colecci?n de Coleoptera (Scarabaeoidea) del sureste de la Pen?nsula Ib?rica de la Universidad de Granada. 348 records from Antarctic pycnogonids. 1 records from Tyrannosaurus was not a fast runner. 62799 records from MLZ Bird Collection (Arctos). 15 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 6 records from 2. Donauinsel bei Entau. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 186 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 370 records from Planktic foraminifera assemblage in sediment core GIK17050-1. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 5 records from DREAL_PACA_-_N2000_-_Office_National_des_For?ts_04_2017_12_18. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1320 records from Ornithologie Federsammlung - SNSD. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 2 records from Perotrochus caledonicus (Gastropoda: Pleurotomariidae) revisited: descriptions of new species from the South-West Pacific. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 385 records from UWYMV Herpetology Collection (Arctos). 46 records from Liether Park (LMS), 5a. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 14069 records from Midden-Limburg Fish Ponds Survey. 92061 records from Herbarium (ICEL). 111684 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1 records from Zetes ephippiatus. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 15826 records from Leiner-Herbar Konstanz. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 895 records from Geometridae de France m?tropolitaine. 105 records from bmhs_moth_collection. 256 records from Cactophilic Drosophila and Opuntia. 20 records from A revision of the genus Navasoleon Banks (Neuroptera: Myrmeleontidae: Nemoleontini). 4 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 232 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 174 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 2 records from Umbellula pomona sp. nov., a new sea pen from Mar del Plata Submarine Canyon (Cnidaria: Octocorallia: Pennatulacea). 44419 records from WCPS Bird Survey Project. 9 records from Planktic foraminifera abundance of Hole 4-26. 106 records from Sylter Meerstrandl?ufer. 717 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 237 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 32537 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 1383 records from Plant observations from Bia?owie?a National Park. 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 880 records from Diversity of Spiders from Azorean Trails. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 10354 records from Inventaire de la flore de Charente-Maritime 2018. 2012 records from Pollen profile RAC20, Lake Racou, France. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 7 records from Range table from planktonic foraminifers in ODP Hole 151-912C. 3 records from Some new brachypterous cockroaches (Blattodea: Blaberidae: Epilamprinae) from the Philippines. 225 records from Tillegg R?tinga i Os. 28 records from Donn?es naturalistes de Franck MERLIER. 192 records from Total foraminifera counts of multinet M10/2_MSN218. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 1379 records from (Table 9) Distribution of planktonic foraminifers in ODP Site 112-687. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 21 records from Characterization of Microbial Community Structure and Population Dynamics of Tetrachloroethene-Dechlorinating Tidal Mudflat Communities using a Multipronged Approach. 8654 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 10898 records from Inventario de Hymen?ptera; paras?tica en M?xico. 3 records from A new species of the genus Cyparium from northern Sulawesi, Indonesia (Coleoptera: Staphylinidae: Scaphidiinae). 1 records from A new Atheta species from the West Caucasus and a redescription of A. brevapicalis (Coleoptera: Staphylinidae: Aleocharinae). 873 records from Programme ACT : R?partition Geai des ch?nes 2008 - 2012 Coordonn?es GPS Lambert 93. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 42 records from Occurrence of mammalia relicts at site l?Abri de Campalou. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paran? basin, Brazil. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 50 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 31 records from Bulletin d'informations de l'Association fran?aise de Lich?nologie. 38 records from Nannofossil abundance of Hole 10-89. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 91 records from Nannofossil abundance of Hole 30-285A. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 356 records from Morphologische Daten von Puffinus creatopus. 23648 records from WTSWW Data: All Taxa (West Wales). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 148 records from Herbarium BSG Hepaticopsida. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 20 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 361 records from Nannofossil abundance of Hole 66-490. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 130 records from Synth?se de la R?partition des populations de bouquetin des alpes en 2005 (r?seau Ongul?s sauvages ONCFS-FNC-FDC). 4000 records from Fossil Specimens of Komatsu City Museum. 449 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 238 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 9 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 446 records from Programme ACT : R?partition Etourneau sansonnet 2006 - 2010 Coordonn?es GPS Lambert 93. 3327 records from BioGIS - Mammals - SPNI. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Direcci?n General de Medio Natural y Pol?tica Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 ?m fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 ?m. 194 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 42702 records from MfN - Fossil vertebrates IV. 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 3439 records from MEXU/Flora de Oaxaca. 49536 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 207 records from Nannofossil abundance of Hole 66-488. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crust?ceos, equinodermos y peces) del Santuario Islas e Islotes de Bah?a Chamela, Jalisco, M?xico. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 9304 records from Echinoderm collection of National Museum of Nature and Science. 57 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 2933 records from Donn?es naturalistes d'Alain BERLY. 109176 records from Herps Specimens. 39139 records from Insect Collection from the Museu Nacional de Hist?ria Natural e da Ci?ncia, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 6 records from A new fossil species of Trentepohlia (Diptera, Limoniidae) from the Dominican Miocene. 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 250 records from Inventaire et regroupement de donn?es Natura 2000. 12724 records from Donn?es bibliographiques et opportunistes Mammif?res du Nord Pas-de-Calais issues du SIRF. 638057 records from Donn?es de la flore d?Alsace (SBA). 18 records from Pygmy grasshoppers of the genus Formosatettix Tinkham? 1937 (Orthoptera: Tetrigidae: Tetriginae). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Donn?es Mammif?res Midi-Pyr?n?es enregistr?es dans BazNat - Lot 1. 384 records from Nannofossil abundance of Hole 17-167. 292 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 289 records from bmhs_butterfly_collection. 1 records from Beitr?ge zur Kenntnis pal?arktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 3812 records from Microbial communities associated with ferromanganese nodules and the surrounding sediments. 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 172 records from checklist-of-birds-of-zomba-mountain. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 423 records from Programme ACT : R?partition Caille des bl?s 2008 - 2012 Coordonn?es GPS Lambert 93. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 1560645 records from Flore Franco-Belge. 62709 records from EAC - Herb?rio Prisco Bezerra. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1564 records from Leif Richardson Vermont Bee Specimens. 247 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur ? ventre jaune - ?tude de r?partition. 29648 records from Collection Crustacea - ZMB. 1 records from A gall mite, Aceria rhodiolae (Acari: Eriophyidae), altering the phytochemistry of a medicinal plant, Rhodiola rosea (Crassulaceae), in the Canadian Arctic. 742 records from Estudio herpetofaun?stico de la Sierra Mazateca, Oaxaca, M?xico. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 290 records from Donn?es 2016 P?lobate brun Comit? D?partemental de Protection de la Nature et de l'Environnement. 5 records from Oosagitta gen. nov. from tropical Africa, with revision of two species and description of four new species (Coleoptera: Chrysomelidae, Galerucinae). 60311 records from LiquenCAT: Banco de datos de los l?quenes de Catalu?a. 156 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 5 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 27 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2316 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras de 2009 a 2014. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 3035 records from ZUEC-OPH - Cole??o de Ophiuroidea do Museu de Zoologia da UNICAMP. 183 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 479 records from CBS Bacteria Database. 214 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 20 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 10654 records from Bryophyte specimens of The Nagoya University Museum. 1860 records from Estudio poblacional del chano norte?o, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies end?micas del Alto Golfo de California, M?xico. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 34520 records from University of Guam Insect Collection. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 1 records from A new species of the mesopelagic isopod genus Xenuraega Tattersall, 1909 (Crustacea: Isopoda: Aegidae) from Japan, the second species in the genus. 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 151 records from Monocotiled?neas del cerro Tacarcuna-Choc?, en el marco del proyecto Colombia BIO 2017. 391 records from Planktic foraminifera abundance of Hole 32-310. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 19 records from Dinoflagellate abundance of Hole 81-554. 5420 records from Donn?es des membres de l'Association fran?aise d'Arachnologie. 174 records from Artenvielfalt des "Gr?nen Klassenzimmers". 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 69 records from Aves Argentinas / Asociaci?n Ornitol?gica del Plata - Colecci?n de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 2814 records from Chronicle of Nature - Phenology of Birds of Pinezhsky State Nature Reserve. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 208 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 85 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 102 records from Nannofossil abundance of Hole 24-232. 1 records from Ueber eine noch nicht beschriebene Nothrus-Art. 31 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 2 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 5 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 1189 records from UWIZM Molluscs. 781 records from Aves Argentinas / Asociaci?n Ornitol?gica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campa?a enero 2011. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 5514 records from MCP-Aves - Cole??o de Aves. 74 records from ?rea Selva de Florencia- Cantidad de ?rea ocupada selva_2018. 3 records from Hidden diversity in European bees: Andrenaamieti sp. n., a new Alpine bee species related to Andrenabicolor (Fabricius, 1775) (Hymenoptera, Apoidea, Andrenidae). 135 records from Nannofossil abundance of Hole 36-329. 4 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 29 records from The genus Chalybion Dahlbom, 1843 (Hymenoptera: Sphecidae) from Northwest Vietnam, with description of a new species. 100 records from Nematode genera abundances at the Arctic H?kon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 147 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 ?m. 76704 records from EDP Foz Tua: Terrestrial Birds, Spring (point counts) - Ecological Monitoring Program [2011-2017]. 824 records from Bird specimens of Saitama Museum of Natural History. 382 records from orthopteracollections-nhmj-ioj. 2 records from Carnivores of Syria. 1058 records from Vertebrados terrestres de San Juan de Camarones, Durango. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 9723 records from The Indigo Project: a global citizen science Ocean survey. 306 records from Diagnostic des Espaces Naturels Sensibles des Yvelines. 7 records from A new species of the genus Takydromus (Squamata, Lacertidae) from southwestern Guangdong, China. 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colecci?n de mariposas del Museo de Entomolog?a de la Universidad del Valle. 55 records from Temporary expansion to shelf depths rather than an onshore-offshore trend: the shallow-water rise and demise of the modern deep-sea brittle star family Ophiacanthidae (Echinodermata: Ophiuroidea). 59828 records from Polish gene bank ? passport data of plants accessions which are important in human life. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1513 records from M. Gollop Collection. 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 16203 records from SMDB - Santa Maria Departamento de Biologia. 1 records from Donn?es naturalistes d'Olivier DELZONS. 53264 records from Naturalis Biodiversity Center (NL) - Diptera. 8 records from The genus Thoradonta in Thailand (Orthoptera: Tetrigidae: Scelimeninae) with description of two new species. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 6 records from Review of the enigmatic genus Boalda with transfer of pulcherrima K?hler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 2 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 673 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 1 records from A New Species Of The Genus Liophloeothrips (Thysanoptera, Phlaeothripidae) From Iran. 13981 records from Flora of the Korean Peninsula. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 106 records from Distribution of planktic foraminifera (125-250 ?m) of box sediment core PS1246-2. 16 records from Hazel Dormouse in Ireland. 602 records from Planktic foraminifera abundance of Hole 9-78. 272 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 8363 records from Colecci?n de Bruniales, Buxales, Canellales y Caryophyllales del Museo Bot?nico CORD - IMBIV. 588 records from Agroforestry plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 1027 records from Programme ACT : R?partition Merle noir 1996 - 2000 Coordonn?es GPS Lambert 93. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 11 records from Revision of the Ulopinae leafhoppers (Hemiptera: Cicadellidae) of the Indian subcontinent, I. Ulopini genera: Daimachus, Radhades and Ulopsina. 115 records from Total foraminifera counts of multinet M21/4_MSN694. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 724 records from There are 3 zooplankton samples from 3 different ponds, we collected sample and use the fresh samples to do DNA extraction directly, then mix them with adjustment guided by the number of species within each of them. At last, use Hiseq-2599 PE-150 to do NGS work. 1 records from New genus and species of the family Niphargidae (Crustacea: Amphipoda: Senticaudata), Chaetoniphargus lubuskensis gen. nov., sp. nov. from Croatia. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 5 records from A revision of the genus Saccoglossus (Hemichordata: Enteropneusta: Harrimaniidae) with taxonomic descriptions of five new species from the Eastern Pacific. 185 records from Inventaire des odonates d'int?r?t communautaire. 79 records from Plasm bearing foraminifera counts of multinet M26/1_MSN844. 4 records from Two new species of heavily calcified cyclostome bryozoans from the intertidal of Akkeshi Bay, Hokkaido, Japan. 90 records from Birdrace-Uttenreuther_Spatzenz?hler-Erlangen/H?chstadt. 6 records from The Lanternfly genus Polydictya (Hemiptera: Fulgoromorpha: Fulgoridae) from Sulawesi and neighbouring islands, with the description of three new species. 168 records from Restauraci?n de flora y repoblamiento de fauna nativa en 1,000 hect?reas para el restablecimiento del corredor biol?gico costero en la Laguna Madre, Tamaulipas. 2116 records from Donn?es de la collection de Hubert Piguet - Famille des Elateridae. 27 records from Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (III). 2419 records from Flora de las sabanas inundables de las cuencas de los r?os Bita, Manacac?as y Cravo Sur - SULU II. 1798 records from Insect (KIDR-IN). 635 records from Distribuci?n, estructura poblacional y variaci?n gen?tica de algunas especies de pinos en peligro de extinci?n en M?xico. 1014 records from Programme ACT : R?partition Merle noir 2009 - 2013 Coordonn?es GPS Lambert 93. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 16119 records from marine metagenome Metagenome. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 685 records from Range table from benthic foraminifers in ODP Hole 151-913B. 1 records from A new generic name, Semigothograptus, for Gothograptus? meganassa Rickards & Palmer, 2002, from the Silurian post- lundgreni Biozone recovery phase, and comparative morphology of retiolitids from the lowermost upper Homerian (upper Wenlock). 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 259 records from Programme ACT : R?partition Alouette lulu 2009 - 2013 Coordonn?es GPS Lambert 93. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 2102 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales ?Florentino Ameghino?, Santa Fe, Argentina - Colecci?n Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 25446 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 7839 records from Inventario flor?stico de la regi?n Calakmul-parte baja de la regi?n Lacandona (Cuenca alta del Usumacinta y Marqu?s de Comillas). 5316 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 36 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 5 records from First record of the genus Chandleriella Hlav?? (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 12127 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 28 records from Korean Plant Virus Database. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 52 records from Herbarium Senckenbergianum (FR) - Protista. 250 records from Colecci?n de helechos de la FML. 3 records from Zoology in the Middle East. 24 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 68916 records from Donn?es de l'Observatoire de la Faune de Bourgogne. 1184 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 255 records from Programme ACT : R?partition Perdrix rouge 2009 - 2013 Coordonn?es GPS Lambert 93. 4447 records from Colecci?n Herpetol?gica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 539 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 150 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 5915 records from Museu de Ci?ncies Naturals de Barcelona: MCNB-Tissue. 321 records from Echinoderms from the Seaflower Biosphere Reserve. 198 records from Programme ACT : R?partition Alouette lulu 1996 - 2000 Coordonn?es GPS Lambert 93. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 117 records from Nannofossil abundance of Hole 49-408. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 17 records from Analyses of the recent components of sediment core PS1011-1. 69 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 208 records from Chapter 7: Linnaean Plant Names and their Types (part V). 32 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 6 records from Foraminifera abundance of Hole 58-442. 10122 records from Uncultured eukaryotes Targeted Locus (Loci). 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 396 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 13 records from Cole??o de Coleoptera da Universidade de Bras?lia. 83 records from Aves Argentinas / Asociaci?n Ornitol?gica del Plata - Colecci?n de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 98 records from Warnowtal (Rostock). 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from C?digo de barras de ejemplares de la Colecci?n Nacional de Mam?feros del Instituto de Biolog?a, UNAM. 2747 records from Compost microbe establishment and growth in agricultural soils. 202122 records from National Benthic Inventory. 50 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 109 records from MMFR Zingiberaceae Botanical. 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 30 records from Nannofossil abundance of Hole 9-82. 2660 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 1939 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 102 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Gro? Klein. 153 records from Planktic foraminifera abundance of Hole 18-181. 21 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 23238 records from Sistem?tica e historia natural de algunos anfibios y reptiles de M?xico. 88 records from BOTU-Fungi - Herb?rio Irina Delanova Gemtch?jnicov - Cole??o de Fungos. 238 records from Evaluaci?n del ?mbito hogare?o y calidad de h?bitat del borrego cimarr?n (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Bi?sfera El Pinacate y Gran Desierto de Altar. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 343 records from Programme ACT : R?partition Caille des bl?s 2012 - 2016 Coordonn?es GPS Lambert 93. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 76 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 2 records from Microfossil abundance of Hole 21-208. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 86676 records from Marine Offshore Seabed Survey data held by JNCC. 13 records from Benthic foraminifera abundance of Hole 96-620. 99 records from Nanoplankton abundance at station GeoB2006-4. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 319 records from Donn?es naturalistes de Monsieur LEFEBVRE Fran?ois. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 452759 records from Herbarium of Taiwan Forestry Research Institute. 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 23 records from Ackerrain Pl?nhagen. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Donn?es odonates. 258 records from Malawi-Histeridae-Biodiversity-Data. 1286 records from Planktic foraminifera abundance of Hole 7-64. 29 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 85 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pr?-Guittard, SE France. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 1 records from Oribates calcaratus. 502808 records from The cryptogamy collection (PC) at the Herbarium of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 6417 records from Actualizaci?n y depuraci?n de las bases de datos de la Colecci?n Nacional de Helmintos: P085 y Q028. 4644 records from Recensement et distribution Mammif?res marins Guadeloupe Antilles fran?aises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4046 records from Consolidaci?n de la colecci?n de referencia de peces de la Estaci?n Mazatl?n, (ICMyL-UNAM) e implementaci?n de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 272 records from Inventaire malacologique des murs restaur?s en pierre s?che en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyac?. 2225 records from Donn?es naturalistes d'Ana?s MAS. 2430 records from Microbial community diversity in Arctic marine sediments and Planktonic microbial. 862 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 9997 records from The Myriapoda & Onychophora collection (MY) of the Mus?um national d'Histoire naturelle (MNHN - Paris). 65 records from Donn?es du/de la naturaliste Thibault Marie Th?r?se provenant de la base de donn?e du SINP ?le-de-France CETTIA. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 6 records from Abundance of benthos infauna at station GIK23065-1. 1205 records from uncultured eukaryote Raw sequence reads. 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 4 records from Planktic foraminifera abundance of Hole 17-166. 283 records from Flux data of NU2_trap (Table A1). 11 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 2842040 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 21 records from Two new species of Brueelia K?ler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterizaci?n Ecol?gica de la Fauna del P?ramo de Frontino o del Sol. 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 5346 records from Sediment metagenome. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 71494 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 400 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 14 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colecci?n, preservaci?n y caracterizaci?n de cultivares criollos de origen espa?ol de trigo y centeno de M?xico. 19665 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba. 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 44 records from Mam?feros peque?os en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 817 records from Programme ACT : R?partition Tourterelle turque 1997 - 2001 Coordonn?es GPS Lambert 93. 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 243 records from Thistles species and abundance. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 6 records from Mammalia (JNHM-MM). 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 13947 records from The Vascular Plants Collection of the University of Goettingen. 29559 records from Occurrences de vecteurs de maladies recens?es ? l'H?pital de M?nontin. 2111 records from Flora vascular acu?tica de la cuenca del R?o Tames?. 4962 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 2718 records from Donn?es de la R?serve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2563 records from Phenological Center - Plants (Laplandskiy). 159 records from Caddisflies (Insecta: Trichoptera) from Maranh?o State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 572 records from Benthic foraminifera abundance of Hole 84-567A. 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 453 records from Colecci?n de Fauna Marina del Centro Oceanogr?fico de M?laga (I.E.O.): CFM-IEOMA. 9120 records from ICEL (Land - Invertebrates). 29034 records from UTEP Herpetology (Arctos). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 14965 records from Biological Reference Collections ICM-CSIC. 6 records from First Record of Dericorys albidula Serville, 1838 (Orthoptera: Dericorythidae) in Tunisia and Libya. 127 records from Total foraminifera counts of multinet POS247/2_MSN1380. 2497 records from Donn?es des collections d'algues du MNHN. 54 records from Phytoplankton abundance at station Casma_2003-02-27_2, Casma, Peru. 349178 records from AMNH Herpetology Collections. 16257 records from SP-Algae - Herb?rio do Estado "Maria Eneyda P. Kaufmann Fidalgo - Cole??o de Algas. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 137 records from Lynx 2011 pr?sence Occasionnelle Maille 10km R?seau Loup-Lynx ONCFS. 723 records from Aves Argentinas / Asociaci?n Ornitol?gica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campa?a noviembre 2008. 422150 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammif?res marins Guadeloupe Antilles fran?aises (AET). Suppl?ments. 104 records from Urwald 1 (Bad Waldsee). 421965 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 118 records from Observation des insectes sur le territoire de la M?tropole Rouen Normandie. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 10269 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6433 records from Modernisation des ZNIEFF du PnrL. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 601 records from Muestreos y recolectas de flora end?mica y casi-end?mica de matorral costero y chaparral de la zona mediterr?nea Baja California, M?xico. 20 records from Occurrence of mammalia relicts at site Niederlehme. 1264 records from Grand Voyeux - Suivis scientifiques. 46 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 86 records from UWIZM Cnidarians. 356 records from Colecci?n Taxon?mica Nacional de Insectos ?Luis Mar?a Murillo? (CTNI). 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 40339 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 178089 records from Tasmanian Museum and Art Gallery provider for OZCAM. 968 records from TTRS Mammals. 41 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 1001 records from Mushroom (KIDR-MR). 15 records from Neotropical Chvalaea Papp & F?ldv?ri (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 1234 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling at Pathogen Plots]). 492 records from Colecci?n Ornitol?gica Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 876 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Occurrence of mammalia relicts at site High Furlong. 2899 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-K?stner-Schule erforscht das Bachemer Wiesental. 2741 records from Bryozoa, Brachiopoda and Entoprocta from the collection of the Arctic University Museum of Norway in Troms?. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 48 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 1 records from A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters. 134 records from Faunal assemblage of sediment core TR149-32. 787 records from Programme ACT : R?partition Pie bavarde 2009 - 2013 Coordonn?es GPS Lambert 93. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1 records from Aves Argentinas / Asociaci?n Ornitol?gica del Plata - Colecci?n de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 54 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 1 records from Hoplophora ardua. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 1 records from Memecylon pseudomegacarpum M. Hughes (Melastomataceae), a new species of tree from Peninsular Malaysia. 111 records from Birdrace-Uhulogen-Lippe. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 7010 records from La familia Asclepiadaceae en M?xico. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 11 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Donn?es opportunistes produites par Alexandre RUFFONI dans le cadre de l??laboration d?un guide de d?termination des larves de pl?copt?res. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopaloc?res de France (STERF). 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 1000 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 49 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 561 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 61 records from Alien Species in Poland - Plants. 401 records from Donn?es de VINCENT Alexis (SAPROX). 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Donn?es de la structure For?ts en Aulnoye provenant de la base de donn?e du SINP ?le-de-France CETTIA. 82 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 1 records from Larval morphology of Plagiosterna adamsii (Baly) and P. aenea (Linnaeus) with resurrection of Gastrolinoides Ch?j? & Kimoto and P. formosana (Bates) (Coleoptera: Chrysomelidae: Chrysomelinae). 5 records from Two new nematode species of the genus Tobrilus Andr?ssy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 9 records from New data on brown lacewing genus Wesmaelius Kr?ger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 89 records from Type locality records of Polycystididae species in the world. 202057 records from Base de datos de plantas vasculares del Pa?s Vasco: ARAN-EH. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1122 records from Donn?es naturalistes de St?phane ORIO. 665 records from Collection Echinodermata - ZMB. 442 records from Inventario herpetofaun?stico del noroeste de Hidalgo. 32640 records from EDP Foz-Tua: Macrophytes ? Ecological Monitoring Program [2011-2015]. 244 records from WildesMoor bei Schwabstedt. 3182 records from The Paleontological Collections at the Bayerische Staatssammlung f?r Pal?ontologie und Geologie. 379 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 25 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 212 records from Donn?es des naturalistes POHIER et LEFORT provenant de la base de donn?e du SINP ?le-de-France CETTIA. 268 records from Bri?fitos del cerro Tacarcuna-Choc?, en el marco del proyecto Colombia BIO 2017. 234 records from CNMA/Colecci?n de Mam?feros de la Estaci?n de Biolog?a Chamela. 98 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 33 records from Synopsis of warty leaf beetle genera of the world (Coleoptera, Chrysomelidae, Cryptocephalinae, Chlamisini). 2326 records from Jard?n Bot?nico Atl?ntico, Gij?n: JBAG. 1 records from First record of Caliscelis (Caliscelis) bonellii (L, 1807) (Hemiptera: Fulgoromorpha: Caliscelidae) from Turkey, with redescription of the species. 36 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 3990 records from Donn?es rhopaloc?res collect?es par le CEN Aquitaine entre 1970 et 2015. 349 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Donn?es sur les Opisthobranches et Planaires de Mayotte. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 129 records from Planktic foraminifera abundance of Hole 94-611. 105 records from Lynx 2015 pr?sence Occasionnelle Mailles_10km_LAEA R?seau Loup-Lynx ONCFS. 91253 records from CUMV Fish Collection. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 6922 records from MUST, Insecta. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 1027799 records from Donn?es ONF faune-flore-fonge. 2116 records from Collection entomologique Pierre Lachiver. 2 records from A taxonomic study on the Bornean and Philippines Sword-tailed Crickets in the genus Rhicnogryllus Chopard, 1925 (Orthoptera: Trgonidiidae; Trigonidiinae). 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 48 records from Deutsche Schule Budapest. 1463 records from Regroupement de donn?es rhopaloc?res r?colt?es sur la p?riode de 2010-2015 par Cistude Nature. 31 records from Stenus maculifer CAMERON: eine B?chse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 189637 records from University of Michigan Museum of Zoology, Division of Mollusks. 4 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 2 records from New records of Nuuanuidae (Crustacea: Amphipoda: Senticaudata) from Korean waters, with descriptions of one new genus and two new species. 32 records from Site Condition Monitoring of the downy willow Salix lapponum component of the Vascular Plant Assemblage interest of Skinsdale Peatlands SSSI, 2016. 43 records from Aves Argentinas / Asociaci?n Ornitol?gica del Plata - Colecci?n de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 122 records from M. Burton (1936). The Fishery grounds near Alexandria IX ? Sponges. Notes and Memoirs No.17. Department of Zoology, British Museum. Fisheries Research Directorate. Ministry of Commerce and Industry, Egypt.. 3 records from Setaphyes elenae sp. nov., a new species of mud dragon (Kinorhyncha: Allomalorhagida) from Skagerrak (north-eastern Atlantic Ocean). 5 records from Occurrence of mammalia relicts at site Siebenlinden 3. 19651 records from Estudios bi?ticos (Plantas, Fauna Ed?fica, Anfibios y Aves) en los Complejos de p?ramos Tota-Bijagual-Mamapacha. 3 records from Review of the fossil record of Bittacomorphinae (Diptera: Ptychopteridae). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 275 records from Range table from benthic foraminifers in ODP Hole 144-874B. 29912 records from Donn?es acquises via le r?seau du Conservatoire botanique national du Bassin parisien. 2340 records from Type Specimen Database of Museum and Institute of Zoology PAS. 62161 records from DASSH Data Archive Centre Academic Surveys. 75 records from Annotated type-catalogue of Brachyura (Crustacea, Decapoda) of the Mus?um national d?Histoire naturelle, Paris. Part II. Gecarcinidae and Grapsidae (Thoracotremata, Grapsoidea), with an Appendix of pre- 1900 collectors. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 116 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 513 records from Quoll sightings register for Nth QLD. 9 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 55 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 1 records from A new species of Ischyomius from Venezuela (Coleoptera, Tenebrionoidea, Pythidae) with a revised key to world species. 6 records from Alburnus magnificus, a new species of bleak from the Orontes River drainage (Teleostei: Leuciscidae). 384654 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herb?rio Virtual REFLORA. 8 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from Donn?es naturalistes de Thibault RAMAGE. 43 records from A revision of the systematics and distribution of the damselfly genus Prodasineura Cowley, 1934 (Odonata: Zygoptera: Platycnemididae) in Vietnam with description of two new species. 43 records from Vogelstimmenf?hrung durch den Tiergarten. 448 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 11 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 2975 records from Tetr?podos de Uruguay. 4 records from Craspedotropis gretathunbergae, a new species of Cyclophoridae (Gastropoda: Caenogastropoda), discovered and described on a field course to Kuala Belalong rainforest, Brunei. 2 records from Phylogenetic analysis and systematic position of two new species of the ant genus Crematogaster (Hymenoptera, Formicidae) from Southeast Asia. 195 records from Donn?es de la naturaliste Giordano Charlotte provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3 records from Larval morphology and life history of Eutrichosoma mirabile Ashmead and description of a new species of Eutrichosoma (Hymenoptera, Chalcidoidea). 22 records from Propri?t? r?gionale du Moulin des Marais - Inventaire naturaliste 2015. 12 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 36 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 7 records from Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China. 7601 records from University of Kentucky Insect Collection. 51903 records from Atlas des Orthopt?res et Mantides de France m?tropolitaine. 35 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 64 records from Donn?es du/de la naturaliste Bourdin Dominique provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2 records from A remarkable burrow-dwelling alpheid shrimp, new genus and new species, from the tropical eastern Pacific (Malacostraca: Decapoda: Caridea). 1418 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 2 records from Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula. 24 records from Ostracoda abundance of Hole 48-406. 391 records from GEOECOLINK_2017_12_18. 111 records from Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila). 2233 records from UTEP Herpetology Osteology (Arctos). 3 records from New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China. 21 records from A survey of Agroeca Westring, 1861 from China (Araneae: Liocranidae). 2 records from Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae). 135998 records from The Scottish Squirrel Database. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 13 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 47 records from Planktic foraminifera counts of sediment core V26-124. 11 records from Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records. 168 records from Caracterrizaci?n flor?stica del humedal La Abuelita, Municipio de Guapi-Cauca, 2018. 36 records from Selz (Ingelheim am Rhein). 398 records from Tsetse flies of East Africa update. 4 records from A new species of Heliothrips (Thysanoptera, Panchaetothripinae), based on morphological and molecular data. 8 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 20755 records from pins. 3 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 1005 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los r?os Bita, Manacac?as y Cravo Sur - SULU II. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 772 records from FBIP: Baboon spider distribution records from selected South African museums. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 80 records from The Pyraloidea (Lepidoptera) fauna of the woody savannah belt in Mali, West Africa. 285 records from Donn?es du/de la naturaliste Cousin Richard provenant de la base de donn?e du SINP ?le-de-France CETTIA. 5 records from A new micropterous winter species of Leuctra (Plecoptera: Leuctridae) and little known endemic stoneflies from the Greater Caucasus. 540 records from Foraminifera abundance of Hole 74-526A. 71 records from ZUEC-ECH - Cole??o de Echinoidea do Museu de Zoologia da UNICAMP. 1895 records from Donn?es opportunistes amphibiens-reptiles du Nord et du Pas-de-Calais. 1455 records from Records of Halicarcinus planatus at sub-Antarctic regions. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis H?bner (Lepidoptera: Tortricidae). 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 600 records from Colecci?n de Herpetolog?a de la Universidad del Quind?o (HERPETOS-UQ). 48 records from Planktic foraminifera abundance of Hole 6-47. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 51 records from Nannofossil abundance of Hole 20-199. 569 records from Counts of the living benthic foraminifera assemblage in surface sediments of the North Atlantic. 237 records from Planktic foraminifera abundance of Hole 21-207. 15 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 356 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 91 records from Gemeinschaftsaktion Koordinatoren f?r nachhaltige Bildung/Wittstocker Grundschulen. 1 records from Range table from planktonic foraminifers in ODP Hole 141-862B. 160 records from Donn?es esp?ces - Expertise IPE 37. 431 records from Nannofossil abundance of Hole 74-528A. 11802 records from WOLL AVH data. 6 records from On the Chilopoda from Turkey. 12650 records from Recensement des esp?ces en vue de l'?laboration du r?pertoire des for?ts sacr?es, for?ts galeries, savanes et autres formation floristique du B?nin.. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 203 records from Insectos de la expedici?n al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 154 records from Shannon Index and species richness for arthropods. 50 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 3638 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 67 records from ?rea Las Hermosas - Cantidad area ocupada oso, 2018. 1848 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 200 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 2041 records from marine metagenome Targeted Locus (Loci). 1 records from Occurrence of mammalia relicts at site Ejstrup. 896 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 28385 records from Plan de vertebrados de la Patagonia. 10 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 12869 records from Apoyo a las colecciones biol?gicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 2 records from Myzostoma khanhkhoaensis (Myzostomida), a new myzostomid species from the Nhatrang Bay, Vietnam. 274 records from Planktic foraminifera abundance of Hole 22-217. 3 records from Occurrence of mammalia relicts at site Igstadt I. 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 13000 records from LPO_PACA_2017_12_18. 8 records from Nannofossil abundance of Hole 39-353A. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 232661 records from Oklahoma Vascular Plants Database Provider. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 42 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biol?gicos CIRN-INTA). 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 724 records from Programme ACT : R?partition Faisan commun 2009 - 2013 Coordonn?es GPS Lambert 93. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 6468 records from Computarizaci?n de la Colecci?n de mam?feros del Centro de Investigaciones Biol?gicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 31342 records from Collection Pisces SMF. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 2691 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41553 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 120716 records from Microbial biogeography of 925 geothermal springs in New Zealand. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 1584 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 4 records from One new species of the genus Xizicus Gorochov, 1993 (Orthoptera: Tettigoniidae Meconematinae) from Guangxi, China. 14590 records from Estado actual, identificaci?n de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrol?gicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del r?o de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 ?m fraction. 1863 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 2950 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 326086 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 12 records from On the Neotropical spider genus Tullgrenella Mello-Leit?o, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 17713 records from NCSM Mammals Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 770 records from Niv? Bay species list, Zealand, Denmark. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 171 records from Fungal Bioblitz in Bia?owie?a Primeval Forest at 18th Congress of European Mycologists. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 96290 records from Colecci?n de Entomolog?a del Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-E). 216890 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 14 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 18 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 152 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibd? - Choc?, 2019. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 120 records from Naturschutzgebiet Lochbusch-K?nigswiesen. 70 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 7814 records from Odonata de Veracruz. 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 622 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 92 records from Nottekanal, Klasse 7 - 10. 574 records from Percentages of planktonic foraminifera species in sediment core V30-40. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 4733 records from Inventaire des Mollusques Sphaeriidae de France. 1 records from The fossil crown wasp Electrostephanus petiolatus Brues in Baltic Amber (Hymenoptera, Stephanidae): designation of a neotype, revised classification, and a key to amber Stephanidae. 17073 records from donn?es aran?ologiques de CORNIC Jean-Fran?ois. 742 records from Programme ACT : R?partition Alouette des champs 2000 - 2004 Coordonn?es GPS Lambert 93. 477 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 2929 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 884 records from Sea shells of New South Wales. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4222 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geogr?fico y el nicho ecol?gico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 11 records from Late Cretaceous dinosaurs from the Denver Basin, Colorado. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 6927 records from Estudios bi?ticos (Plantas, Fauna Ed?fica, Anfibios y Aves) en los Complejos de p?ramos las Hermosas y Chil?-Barrag?n.. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 5710 records from Colecci?n de Mam?feros del Instituto de Ciencias Naturales (ICN-MHN-Ma). 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 391 records from Vegetaci?n de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 244 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 72170 records from The Environmental Sample Collection of Spiders at the Staatliches Museum f?r Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 16730 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composici?n flor?stica y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimar?es & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 92 records from Planktic foraminifera abundance of Hole 22-212. 2 records from Nannofossil abundance of Hole 4-26A. 45 records from Universit? P?dagogique Nationale de Kinshasa (UPN) - Le b?tail dans la R?publique D?mocratique du Congo (bases de donn?es des animaux ?lev?s pour consommation)- Projet CABIN. 173 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colecci?n de Peces Dulceacu?colas of Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-P), Colombia. 440 records from Wichita State University Collection. 86 records from Donn?es naturalistes de Pierre-Alexis RAULT. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 3 records from Chemistry supports the identification of gender-specific reproductive tissue in Tyrannosaurus rex. 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 647 records from pbzt_insect_biodiversity. 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 281 records from NZCS Upper Tapanahony Expedition 1991. 1 records from Oppia nitens. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 24 records from Tanzanian Vertebrate Collection. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 603 records from Fossil (NSMK-FO). 5 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 16 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 22 records from Ahuyentamiento, rescate y reubicaci?n de fauna en el ?rea de influencia directa del proyecto Hidroel?ctrico Mulatos II. 6652 records from Inventory of plant species through Benin (West Africa). 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 6 records from The bee genus Caenaugochlora (Hymenoptera, Apoidea) and its constituent subgenera, with new species of Caenaugochlora s. str. from Ecuador. 4109 records from South Caribbean Diversity. 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 3 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 873 records from Programme ACT : R?partition Grive musicienne 2006 - 2010 Coordonn?es GPS Lambert 93. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 1741 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 5 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 276 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 1569 records from Pollen record of sediment core Bokanjacko Blato 1. 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 26 records from New acoustic and molecular data shed light on the poorly known Amazonian frog Adenomera simonstuarti (Leptodactylidae): implications for distribution and conservation. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 1 records from Oribates fusifer. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic R?o Sal? basin, Tucum?n, northwestern Argentina.. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 7 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 ?m. 75 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 2 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 1967 records from Fototrampeo de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 16 records from Lepidium campestre In H?fliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 4 records from Rex, sit: digital modeling of Tyrannosaurus rex at rest. 1004 records from Aix-Marseille Universit? - MARS herbarium ? Cytogenetic data-base. 125385 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 3 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 477 records from Planktic foraminifera distribution of sediment core SU81-07. 1645 records from Determinaci?n del estado actual de cinco especies de cact?ceas amenazadas del estado de Tamaulipas, M?xico. 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 1 records from Registro de Ateles belzebuth (mono ara?a) en el municipio de Yopal, departamento de Casanare. 23831 records from RNF - Donn?es du Conservatoire d'espaces naturel Franche-Comt?. 6326 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, M?xico. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 612 records from Deep-sea meiobenthos at Calvi (Corsica) sampled in September 1982. 98 records from Donn?es opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (O?maritz). 74729 records from Synth?se 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recens?e via les portails g?r?s par la LPO de 2013 ? 2017. 16844 records from Donn?es Entomologiques A. HORELLOU 1988-2018. 40 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 3 records from Record of the Non-native Suckermouth armored catfish hybrid Pterygoplichthys pardalis (Castelnau, 1985) x Pterygoplichtys disjunctivus (Weber, 1991) (Siluriformes: Loricariidae) in Honduras. 1023 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 12 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 5314 records from Dados da ocorr?ncia de plantas lenhosas em um gradiente de perturba??o/precipita??o em ?rea de Caatinga, Parque Nacional do Catimbau, Bu?que, PE, Brasil. 11129 records from Royal Ontario Museum Fungarium (TRTC). 3188 records from Butterfly_conservation_2017_12_18. 27 records from Laubwald Dreil?ndereck (Aachen/Vaals[NL]). 137496 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 5 records from Scissurella nesbittae, new species, from the Gries Ranch Formation, Lewis County Washington State (Gastropoda: Vetigastropoda: Scissurellidae). 64 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 15 records from Body Mass, Bone " Strength Indicator, " and Cursorial Potential of Tyrannosaurus rex. 19 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 28637 records from Donn?es bibliographiques et opportunistes Odonates issues du SIRF. 2736 records from Mise en place d'un suivi scientifique des amphibiens pour la production d?indicateurs de biodiversit?. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 6 records from Taxonomic status of the barbastelles (Chiroptera: Vespertilionidae: Barbastella) from the Japanese archipelago and Kunashir Island. 502 records from Metagenome microbial communities of bottom sediments of the Kara Sea. 99 records from D?ne am Ulvenberg (Darmstadt). 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 330 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 7009 records from Mammal osteology MZS. 2656 records from Swiss Psyllid (Hemiptera) Collections - Basel. 14 records from Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species. 45 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 2 records from Spockia tagala gen. and sp. nov. a new monotypic genus of Asopinae (Hemiptera: Heteroptera: Pentatomidae) from the Philippines. 982 records from Pilotoverv?king av dragehode Dracocephalum ruyschiana. 967 records from Planktic foraminifera abundance of Hole 15-148. 260 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 4378 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 187 records from Mollusca specimens of Kuroshio Biological Research Foundation. 425 records from donn?es bibliographiques diverses (non araign?es). 11 records from Barsine wangi, a new species from Guangdong, southern China (Lepidoptera, Erebidae, Arctiinae). 6 records from A new species of salamander of the genus Hynobius (Amphibia, Caudata, Hynobiidae) from South Korea. 59016 records from Isopoda (Interim dataset). 1 records from A new epigean species of the genus Anelpistina (Insecta: Zygentoma: Nicoletiidae) from Sierra de El Abra, Taninul, Mexico. 190 records from Plant macrofossil concentrations from an open section of Lac de Fully sediments. 9 records from A survey of East Palaearctic Gnaphosidae (Araneae). 10. Three new Gnaphosa species from the Dzhungarian Alatau Mountains (Eastern Kazakhstan). 90 records from Microbes in drinking water and biofilms (18S rDNA amplicon study). 1115 records from Ortopteroides de Oaxaca, M?xico: Orthoptera, Mantodea y Phasmatodea. 250336 records from Donn?es faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 177 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 10 records from Lectotype designations, taxonomic notes and new synonymy in some species of the bee genus Centris Fabricius, 1804 described by William Henry Fox (Hymenoptera: Apidae). 474 records from Donn?es du/de la naturaliste VINCENT Sylvain provenant de la base de donn?e du SINP ?le-de-France CETTIA. 9 records from Discovery of Raphidioptera (Insecta: Neuropterida) in Xizang, China, with description of a new species of Inocellia Schneider. 7 records from New species of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae: Meconematini) from Sichuan, China. 3338 records from Algae collection, Oslo (O), Natural History Museum, University of Oslo. 6 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 6 records from Nannofossil abundance of Hole 6-49. 43 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 5061 records from Metagenome from mudbank Area,Alappuzha Kerala India. 5 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 72 records from Planktic foraminifera abundance of Hole 16-161. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 31094 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 323 records from Eco-Strat?gie_2017_12_18. 968 records from Guinea-Bissau Herpetological Collection - IICT. 2 records from Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup). 967 records from Inventaire des Odonates. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 75 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 906 records from C?digos de barras del ADN de mam?feros topotipos de M?xico Fase I: Noroeste mexicano. 3 records from A new species of Schindler's fish (Teleostei: Gobiidae: Schindleria) from the Malay Archipelago (Southeast Asia), with notes on the caudal fin complex of Schindleria. 85 records from Planktic foraminifera counts of sediment core V27-47. 457 records from Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 2190 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 383 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 102 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 23 records from AlgaTerraMovies. 1 records from On the Chilopoda from Turkey. 143 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 829 records from Programme ACT : R?partition Geai des ch?nes 2007 - 2011 Coordonn?es GPS Lambert 93. 107 records from The Stephanidae (Hymenoptera) of Mexico, with description of six new species and key to western Foenatopus Smith. 60 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 1 records from A new garden eel, Heteroconger fugax (Congridae: Heterocongrinae), from the northwestern Pacific Ocean. 306 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 231 records from Epifauna community at Waarde and Saeftinghe (Westerschelde) in 1991. 2 records from Bracon planitibiae sp. nov. (Hymenoptera: Braconidae), a new parasitoid of Asian longhorned beetle (Anoplophora glabripennis). 2 records from A new genus and species of Onciderini Thomson, 1860 (Coleoptera: Cerambycidae: Lamiinae) from Ecuador, with notes on additional taxa. 73579 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 56 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 76 records from Schulgel?nde des Gymnasiums Nepomucenum (Coesfeld). 143 records from Toxicity of copper to three Macquarie Island marine gastropods 2013/15. 4588 records from Bird collection Natuurmuseum Brabant, Tilburg. 7 records from of patch-nosed snake (Colubridae: Salvadora Baird and Girard, 1853) from Oaxaca, Mexico. 3 records from Redescription of Lernaeenicus stromatei Gnanamuthu, 1953 (Copepoda: Siphonostomatoida: Pennellidae) infesting the Black Pomfret Parastromateus niger (Bloch) from Indian waters. 102 records from Benthic foraminifera abundance of Hole 42-372. 1458 records from HUCPE - Herb?rio da Universidade Cat?lica de Pernambuco. 469920 records from Natural England Marine Monitoring surveys. 682 records from Range table from benthic foraminifers in ODP Hole 139-857A. 81 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 126 records from Foraminifera species abundances from tow TT011_10-MOC71. 66 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 42 records from New records of chalcidid (Hymenoptera: Chalcididae) pupal parasitoids from India. 22 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 94 records from Range table from planktonic foraminifers in ODP Hole 170-1040B. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 19 records from Amphicnemis rigiketit sp. nov. from Sarawak, with notes on Amphicnemis remiger Laidlaw, 1912 (Odonata: Zygoptera: Coenagrionidae). 2034 records from Coleoptera Collection. 183 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 415 records from Loup 2016 pr?sence occasionnelle communale (r?seau Loup-Lynx ONCFS). 1429 records from Kangawalla Bird Sightings. 1 records from Nothrus peltifer. 232 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 14 records from Four new species and new records of Manota (Diptera: Mycetophilidae) from Sulawesi, Indonesia. 2184 records from Occurrence (present/absence) and abundance of zooplankton in Murchison Bay, Lake Victoria. 23 records from Ours 2016 pr?sence Occasionnelle Mailles 10km LAEA R?seau Ours brun ONCFS. 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoT? KL71. 3047 records from Cole??o Zool?gica de Refer?ncia da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 67 records from Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex. 9 records from Description of a new species of Ochraethes Chevrolat, 1860, redescription of Plocaederus mirim Martins and Monn?, 2002, and new geographical records for Plocaederus Dejean, 1835 (Coleoptera, Cerambycidae, Cerambycinae). 66 records from SNH Invertebrate Site Condition Monitoring 2013/14: Whitlaw Mosses SSSI. 213 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 5 records from Discovery of a new species of Embolemus Westwood (Hymenoptera: Embolemidae) from New Caledonia. 1 records from Nouvelles fourmis d'Afrique.. 4 records from Polyphasic classification of Nonomuraea strains isolated from the Karakum Desert and description of Nonomuraea deserti sp. nov., Nonomuraea diastatica sp. nov., Nonomuraea longispora sp. nov. and Nonomuraea mesophila sp. nov.. 441 records from L?nea base del medio bi?tico en los bosques dentro de la zona propuesta para Acuerdos de Conservaci?n Voluntaria en la microcuenca de la Quebrada Aguazula - Rinc?n del Soldado_Yopal. 7657 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 3 records from A new record of the genus Orientalicesa Ko?ak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 4 records from Tortonian teleost otoliths from northern Italy: taxonomic synthesis and stratigraphic significance. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10313 records from Donn?es naturalistes d'Olivier GARGOMINY saisies sous cardObs. 16506 records from Database for alien invasive plants occurrences in Germany. 422 records from Aves Argentinas / Asociaci?n Ornitol?gica del Plata - Colecci?n de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 407 records from Strathclyde badger sett surveys 1996-2000. 8 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapaj?s basin, Brazil. 10212 records from Spider (NSMK-SP). 30881 records from OUPR - Herb?rio "Professor Jos? Badini". 10 records from Nannofossil abundance of Hole 58-442B. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotograf?as a?reas en el parque Chingaza. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 12404 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San crist?bal). 3 records from Abundance of zooplankton in the Aral Sea. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 1389 records from Phytoplankton abundance in surface water during cruise CD61. 29 records from Total foraminifera counts of trap L3_92_45. 91 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 374 records from Medicinal potential of African plants (Togo). 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 751 records from Programme ACT : R?partition Pie bavarde 2007 - 2011 Coordonn?es GPS Lambert 93. 13 records from Notes on types of Australian Chartocerus Motschulsky (Hymenoptera: Signiphoridae). 349 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 41 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 8 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 3350 records from Reef Check in Taiwan ???????. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 859 records from Colecci?n Ornitol?gica de la Universidad Tecnol?gica del Choc?. 3178 records from Newfoundland sediment pyrosequencing. 4 records from New morphological information on Simulium wygodzinskyorum Coscar?n & Py-Daniel, 1989 (Diptera: Simuliidae). 16 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 95 records from Conocimiento de la diversidad y distribuci?n actual del ma?z nativo y sus parientes silvestres en M?xico (Tamaulipas). 1120 records from Programme national de science participative sur la Biodiversit? Littorale (BioLit). 6 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 1028 records from Nannofossil abundance of Hole 94-607. 60 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 2171 records from Thrips (Thysanoptera) in Norway. 4065 records from Microbial community in permeable intertidal sediment. 69 records from Entdeckertour am Muldestausee 1/05. 613 records from Implementaci?n de la bioindicaci?n en el R?o Cauca - 2016. 362 records from Mammalian Specimens of the Yamagata Prefectural Museum. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulid?es d'Europe. 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 122 records from BIOTOPE_2017_12_18. 3 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 108 records from BIRDRACE Diesmal sehen wir mehr. 1098 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 977 records from Habitat and host related variation in sponge bacterial communities in Indonesian coral reefs and marine lakes. 36 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1764 records from Arachnida of Costa Rica (INBio). 675 records from Donn?es du naturaliste RADOGEWSKI Alain provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3148 records from Ross A. Layberry, Collection. 3 records from A new species of Mesochra (Copepoda: Harpacticoida: Canthocamptidae) from a coastal system of northern Colombia with a key to the American species. 74 records from Birdrace_G?tkes_Schergen-Helgoland. 1244 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 98 records from Microfossil abundance of Hole 50-416A. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 3 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 24 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 160 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 732 records from DSMZ Collection of Plant Viruses. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 8 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 6 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 451 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 7967 records from Colec??o Entomol?gica do Museu de Hist?ria Natural de Maputo. 18 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 188 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 724 records from Heritage Trees of Ireland. 24 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 613 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 2651 records from Collection Polychaeta - ZSRO. 16774 records from imr_mareano_rpsledge. 140 records from Donn?es du/de la naturaliste LUPOLI ROLAND provenant de la base de donn?e du SINP ?le-de-France CETTIA. 200 records from Bats of Kim Hy Natural Reserve, Vietnam. 90852 records from Herbario de la Facultad de Ciencias Biol?gicas de la Universidad Complutense de Madrid (MACB). 8 records from RISC Non-Native Species Records for Zebra Mussel. 139 records from Nannofossil abundance of Hole 55-433. 17 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 40 records from Revalidation and taxonomic revision of Teloneria Acz?l (Diptera, Neriidae), with description of two new species. 132 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 214 records from Freshwater fish records via iRecord - additional species. 20 records from Abundance of benthos infauna at station GIK23055-1. 2 records from Description of a new whitefly? Pealius satakshiae Dubey (Hemiptera: Aleyrodidae) ? infesting Quercus leucotrichophora (Fagaceae) in the Western Himalaya? India. 3 records from A new species of phlebotomine sandfly, Pintomyia (Pifanomyia) duckei (Diptera: Psychodidae) from Manaus, State of Amazonas, Braz
Keywords: GBIF; biodiversity; species occurrences